Restoring consumer sovereignty : how markets manipulate us and what the law can do about it - Künzler, Adrian (New York, NY : Oxford University Press, 2017)
This work explores the subtle and multifaceted nuances that lead consumers to behave in one way or another. On the whole, the cognitive psychological research has demonstrated that consumer decision-making is a profound topic that is considerably more complex than previously supposed. It is the objective to enable the reader to understand the complexity of individual decision-making, so that legal policy can create environments in which consumers are both better informed, and find more meaning and satisfaction in what they buy.
Specialized.
Description based on online resource; title from home page (viewed on July 31, 2017).
Keywords: Consumer protection -- Law and legislation; Consumers' preferences; Law and economics -- Psychological aspects; Law; Laws of specific jurisdictions & specific areas of law